Astroglial connexins and cognition: memory formation or deterioration?. Issue 1 (10th January 2020) - He, Jin-Ting; LI, Xiao-Yan; Yang, Le; Zhao, Xin
Abstract: Connexins are the membrane proteins that form high-conductance plasma membrane channels and are the important constituents of gap junctions and hemichannels. Among different types of connexins, connexin 43 is the most widely expressed and studied gap junction proteins in astrocytes. Due to the key involvement of astrocytes in memory impairment and abundant expression of connexins in astrocytes, astroglial connexins have been projected as key therapeutic targets for Alzheimer's disease. On the other hand, the role of connexin gap junctions and hemichannels in memory formation and consolidation has also been reported. Moreover, deletion of these proteins and loss of gap junction communication result in loss of short-term spatial memory. Accordingly, both memory formation and memory deteriorating functions of astrocytes-located connexins have been documented. Physiologically expressed connexins may be involved in the memory formation, while pathologically increased expression of connexins with consequent excessive activation of astrocytes may induce neuronal injury and cognitive decline. The present review describes the memory formation as well as memory deteriorating functions of astroglial connexins in memory disorders of different etiology with possible mechanisms.